Shelf-life analysis of lawa mairo frozen as tradisional food from South Sulawesi - Rasmini, Rasmini; Susilowati, Aryanti; Khairiyah, Zul (Sangia Research Media and Publishing, 2024)
This study aims to determine the frozen shelf life of Lawa’ Mairo by analyzing the total plate number. This research was carried out in June 2022, the manufacture and testing of Lawa 'Mairo was carried out at the Laboratory of the Fishery Product Quality Application Center, Makassar, South Sulawesi. This research is classified as quantitative research with experimental method, with four treatments (storage time). Three lengths of frozen storage, namely 1 day, 3 days, and 5 days, as well as 0 days as control (fresh lawa' mairo). Data analysis used the t test to see the effect of storage time on microbial growth and the effect of sensory values on treatment. The results of this study indicate that the shelf life of frozen lawa' mairo from ALT testing that has been carried out is classified as safe for consumption. Lawa’ mairo can last as long as in cold or frozen conditions. Based on the t test, the storage time was declared to have a significant effect on microbial growth in frozen lawa' mairo products. The results of the sensory test on the hedonic scale showed that the panelists' preference level was highest on fresh lawa' mairo (0 days storage). Based on the panelists' assessment of frozen lawa' mairo, there was a change in taste due to an oxidation process during the storage period. Based on the t test performed, it is stated that it has a significant effect between the sensory values of the hedonic scale on the storage time (p<0.05).